2009
DOI: 10.1111/j.1467-8683.2009.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in Corporate Governance: A Review and Proposal

Abstract: Manuscript Type: ConceptualResearch Question/Issue: In this paper we identify and discuss the relationship between corporate governance and risk management of high technology firms, with publicly listed Australian biotechnology companies as a case in point. We present a governance structure that better manages the numerous complex risks such companies face. Research Findings/Insights: Audit committees are traditionally responsible for oversight of auditing matters relating to the company's financial systems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 26 publications
4
91
0
1
Order By: Relevance
“…Several interesting lines of inquiry derive from prior work in strategic management and organizations that could inform research on ERM implementation. For example, corporate governance scholars could examine the role of boards, ownership concentration and executive compensation in ERM implementation (Brown et al, 2009;Carpenter et al, 2003;Isaksson and Kirkpatrick, 2009;Wright et al, 2007). While finance and accounting scholars have studied corporate boards, their emphasis on agency theory has restricted their view to emphasize boards' control function and ignored their advice function (Westphal, 1999).…”
Section: Implementing Ermmentioning
confidence: 99%
“…Several interesting lines of inquiry derive from prior work in strategic management and organizations that could inform research on ERM implementation. For example, corporate governance scholars could examine the role of boards, ownership concentration and executive compensation in ERM implementation (Brown et al, 2009;Carpenter et al, 2003;Isaksson and Kirkpatrick, 2009;Wright et al, 2007). While finance and accounting scholars have studied corporate boards, their emphasis on agency theory has restricted their view to emphasize boards' control function and ignored their advice function (Westphal, 1999).…”
Section: Implementing Ermmentioning
confidence: 99%
“…Due to increased workloads and responsibilities, scholars have suggested that it has gone beyond the scope and capabilities of audit committees to oversee the risk management functions of companies (Brown, Steen and Foreman, 2009). Similarly, Daly and Bocchino (2006) revealed that audit committee members feel that they have too much responsibility and do not have the time or inclination to oversee risk management.…”
Section: Risk Management Committeementioning
confidence: 99%
“…In general, audit committees are focused on the oversight of financial reporting risks and related compliance risks rather than a wider scope for risk management (Brown, Steen and Foreman, 2009;Xie, Davidson, and DaDalt, 2003). Therefore, it is suggested that audit committees may have insufficient skills for overseeing nonfinancial risks, such as operational, strategic, and regulatory risks (Brown, Steen and Foreman, 2009;Daly and Bocchino, 2006).…”
Section: Risk Management Committeementioning
confidence: 99%
See 2 more Smart Citations